PENINGKATAN PEMBELAJARAN GERAK DASAR RENANG DENGAN PENDEKATAN BERMAIN SISWA KELAS IV SDN 125 KECAMATAN PEKANBARU KOTA, KOTA PEKANBARU - Yim Erliza (Jurnal Educhild : Pendidikan dan Sosial, 2018)
This study aims to determine the improvement of basic swimming motion learning through theplay approach. Whether through the play approach can improve the basic motion learning ofswimming, which includes: the process of teacher learning and student participation in learningactivities. The research was carried out on the fourth grade students of SDN 125 Pekanbaru, thenumber of students was 22 people. The process of collecting data uses observation techniques.The observation technique was carried out by observing the process of teacher learning andstudent participation by using observation sheets, which were carried out by two collaborators.After the Improvement of Learning with the Play Approach there was an increase in studentlearning outcomes in the first cycle (59.10%) 13 students successfully completed and in thesecond cycle increased student learning outcomes (86.37%) 19 students successfully completed.It can be concluded that student learning outcomes have increased from cycle I to cycle II amountingto (27.27%) results of posttest, to determine the ability of students to master the lessons in thefirst cycle obtain an average grade of 78.36 while in the second cycle obtain an average classamounting to 82.22. The author concludes that student learning outcomes from cycle I to cycle IIexperience a very significant increase. Penelitian ini bertujuan untuk mengetahui peningkatan pembelajaran gerak dasar renang melaluipendekatan bermain. Apakah melalui pendekatan bermain dapat meningkatkan pembelajarangerak dasar renang, yang meliputi : proses pembelajaran guru dan partisipasi siswa dalamkegiatan pembelajaran. Penelitian dilaksanakan pada siswa kelas IV SDN 125 Pekanbaru jumlahsiswa 22 orang. Proses pengumpulan data menggunakan teknik observasi. Teknik observasidilakukan dengan mengamati proses pembelajaran guru dan partisipasi siswa denganmenggunakan lembar observasi, yang dilakukan oleh dua orang kolaborator. Setelahdilaksanakannya Peningkatan Pembelajaran dengan Pendekatan Bermain terjadi kenaikan hasilbelajar siswa pada siklus I (59,10%) 13 siswa berhasil tuntas dan pada siklus II mengalamikenaikan hasil belajar siswa (86,37%) 19 siswa berhasil tuntas. Dapat disimpulkan bahwahasil belajar siswa mengalami kenaikan dari siklus I ke siklus II sebesar (27,27%) Hasil postest,untuk mengetahui kemampuan siswa menguasai pelajaran pada siklus I memperoleh rata-ratakelas 78,36 sedangkan pada siklus II memperoleh rata-rata kelas sebesar 82,22. Penulismenyimpulkan hasil belajar siswa dari siklus I ke siklus II mengalami kenaikkan yang sangatsignifikan.